2015
DOI: 10.1021/jf506279x
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Exogenous Application of Abscisic Acid Reduces Internal Browning in Pineapple

Abstract: Internal browning (IB) is a postharvest physiological disorder causing economic losses in pineapple, but there is no effective control measure. In this study, postharvest application of 380 μM abscisic acid (ABA) reduced IB incidence by 23.4-86.3% and maintained quality in pineapple fruit. ABA reduced phenolic contents and polyphenol oxidase and phenylalanine ammonia lyase activities; increased catalase and peroxidase activities; and decreased O2(·-), H2O2, and malondialdehyde levels. This suggests ABA could c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…This paradoxical phenomenon might be due to the profiles of accumulated flavonoids, which were determined from not only the involvement of key genes in the biosynthesis pathway, such as 4CL, CHS, OMT, FLS and AOMT; but also, from the blocking of the ABA biosynthesis pathway by NDGA. It was reported that the polyphenolic biosynthesis and the internal browning in postharvest pineapple were inhibited by the application of 380 µM ABA, due to the improved activity of antioxidant enzymes [29]. It was notable to mention that both MLT and ABA promoted flavonoid biosynthesis; therefore, is there any possible interaction between the influences resulted from exogenous MLT and ABA?…”
Section: Discussionmentioning
confidence: 99%
“…This paradoxical phenomenon might be due to the profiles of accumulated flavonoids, which were determined from not only the involvement of key genes in the biosynthesis pathway, such as 4CL, CHS, OMT, FLS and AOMT; but also, from the blocking of the ABA biosynthesis pathway by NDGA. It was reported that the polyphenolic biosynthesis and the internal browning in postharvest pineapple were inhibited by the application of 380 µM ABA, due to the improved activity of antioxidant enzymes [29]. It was notable to mention that both MLT and ABA promoted flavonoid biosynthesis; therefore, is there any possible interaction between the influences resulted from exogenous MLT and ABA?…”
Section: Discussionmentioning
confidence: 99%
“…China produced approximately 1.89 million tons of pineapple in 2014, accounting for 7.4% of worldwide production (FAO, 2014). Under natural conditions, pineapples undergo internal browning (IB) during postharvest storage (Zhang et al, 2015). Therefore, the quality and storage potential of this fruit must be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the quality and storage potential of this fruit must be improved. Effective methods to delay the development of IB include 1-methylcyclopropene treatment (Selvarajah et al, 2001), controlled atmosphere (Nimitkeatkai et al, 2006), waxing (Hu et al, 2012), and exogenous abscisic acid (Zhang et al, 2015), but the mechanism of the IB remains unclear. The recent completion of the pineapple genome has allowed for the genome-wide identification of a number of important gene families (Ming et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, it presents a short postharvest life (Martins et al, 2012). Some efforts have been directed to extend postharvest conservation using cold storage and associated technologies such as plant regulators (Zhang et al, 2015), modified atmospheres , and polysaccharidebased coating (Lima et al, 2012). However, these approaches need to be optimized in terms of improving the barrier properties of the coatings (Dhall, 2013).…”
Section: Introductionmentioning
confidence: 99%